2007
DOI: 10.1145/1273444.1254800
|View full text |Cite
|
Sign up to set email alerts
|

Addressing instruction fetch bottlenecks by using an instruction register file

Abstract: The Instruction Register File (IRF) is an architectural extension for providing improved access to frequently occurring instructions. An optimizing compiler can exploit an IRF by packing an application's instructions, resulting in decreased code size, reduced energy consumption and improved execution time primarily due to a smaller footprint in the instruction cache. The nature of the IRF also allows the execution of packed instructions to overlap with instruction fetch, thus providing a means for tolerating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These enhancements include improving instruction promotion to the IRF,c hanging instruction selection and performing register re-assignment to increase instruction redundancy, and scheduling of instructions to address packing constraints [4]. We also have shown that an IRF can be used to reduce the execution penalty of an L0/filter IC while further reducing energy consumption [5].…”
Section: Progress and Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…These enhancements include improving instruction promotion to the IRF,c hanging instruction selection and performing register re-assignment to increase instruction redundancy, and scheduling of instructions to address packing constraints [4]. We also have shown that an IRF can be used to reduce the execution penalty of an L0/filter IC while further reducing energy consumption [5].…”
Section: Progress and Outcomesmentioning
confidence: 95%
“…We hav e also discovered that an IRF can interact effectively with other instruction fetch energy saving architectural features. Forinstance, we studied howan IRF interacts with an L0/filter IC [5]. Figure 8 shows pipeline diagrams for twoe quivalent instruction streams.…”
Section: Progress and Outcomesmentioning
confidence: 99%
“…Copyright 2010 ACM 978-1-60558-903-9/10/10 ...$10.00. 19,20,21,22,7]; in this paper, we call these L0 instruction stores.…”
Section: Introductionmentioning
confidence: 99%